Clinical Characteristics and Management of Patients With Clinical Amyopathic Dermatomyositis: A Retrospective Study of 64 Patients at a Tertiary Dermatology Department - Tang, Keyun; Zhang, Hanlin; Jin, Hongzhong (Frontiers in Medicine, 2021)
Background Clinical amyopathic dermatomyositis (CADM) represents a subtype of 5-20% of patients with dermatomyositis (DM), which can be categorized into amyopathic dermatomyositis (ADM) and hypomyopathic dermatomyositis (HDM). The characteristics of patients with CADM are still limited in English literature. Objective To investigate clinical features, cutaneous findings, diagnostic accuracy, and treatment regimen of CADM patients. Methods 64 patients diagnosed with CADM at Peking Union Medical College Hospital by dermatologists were retrospectively analyzed. Data were recorded in the electronic database at each offline clinical consultation and directly extracted from medical records. 2017 EULAR/ACR criteria for idiopathic inflammatory myositis (IIM) classification was used to identify and classify patients with CADM. Published studies were searched to extract relevant data of CADM patients. Results This cohort included 38 ADM patients and 26 HDM patients. 2017 EULAR/ACR criteria classified 67.2% of patients with CADM into probable or definite DM. Antimalarials were given to a majority of CADM patients (72.6%, n=45). However, 68.8% (31 out of 45) required at least one aggressive agent combined with hydroxychloroquine due to insufficient response or side effects. The median of systemic treatments in HDM was significantly higher than ADM (p=0.007). The number of ADM patients using antimalarials as monotherapy was significantly higher than that of HDM patients (p=0.031), while the number of HDM patients receiving steroids combined with immunosuppressants was significantly higher (p=0.025). The median of Cutaneous Dermatomyositis Disease Area and Severity Index (CDASI) score improvement was 11.5 and 10.5 for ADM and HDM after a median follow-up of 31.5 and 32.5 months, respectively. 6 patients with normal muscle strength developed muscle weakness after a median of 10.5 months (IQR 9-13), and elevated inflammatory markers at initial visit might indicate their muscle weakness development. Conclusions 32.8% of patients may be overlooked using the three skin variables of 2017 EULAR/ACR criteria. The response rate to single hydroxychloroquine in our cohort was 68.8%. Detailed treatment modalities were different among ADM and HDM. Long-term monitoring for the development of myositis in patients with CADM, especially those with elevated inflammatory markers at initial visit, may be warranted.